Internalisasi Nilai-Nilai Religius pada Pembelajaran PAI - Fibriyan Irodati (LPPM IAINU Kebumen, 2020)
Learning in schools as formal educational institutions has experienced significant development, as seen from the inculcation of religious values ​​in effective religious education learning by touching the learning effect (instructional effect) without leaving the accompanying effect (nurturant effect). This is integrated with continuously increasing the role of religious education in an effort to foster the religious character of its students. Internalization of religious values ​​in PAI learning in schools uses a moral reasoning approach, namely learning that is taken with moral knowledge, moral feelings and moral actions through the internalization process in subject learning activities in class and in self and cultural development programs in schools. The process of internalizing religious values ​​in PAI subject learning activities in class is carried out with procedures for each element of learning activities. The process of internalizing religious values ​​in PAI learning activities in class can employ various methods such as using the role-playing learning model. The process of internalizing religious values ​​in self-development and culture programs in schools for Muslim students is carried out through routine, spontaneous and conditioning activities using habituation strategies through the stages of thinking, recording, repeating, storing, repeating and habituation into character.